2020
DOI: 10.2147/cmar.s276969
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of Immune Checkpoint Inhibitors Plus Chemotherapy on Advanced Gastric Cancer Patients with Elevated Serum AFP or Hepatoid Adenocarcinoma</p>

Abstract: Purpose Alpha-fetoprotein-producing gastric cancer (AFPGC) and hepatoid adenocarcinoma of stomach (HAS) are rare types of gastric cancer, with specific clinical manifestations and poor prognosis. The standardized treatment process of such cancers remains elusive. We aim to investigate the efficacy of immunotherapy combined with chemotherapy on patients with AFPGC or HAS. Patients and Methods AFPGC and HAS patients who underwent immunotherapy and/or chemotherapy as the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
0
26
1
Order By: Relevance
“…The general ORR of chemotherapy in AFPGC was reported to be 8.3% to 66.7% as a first-line therapy, which is quite diverse among different reports because of the small sample sizes. A report of 7 advanced AFPGC patients treated with immunotherapy plus chemotherapy compared with 14 patients as control treated with chemotherapy with or without herceptin/apatinib as first-line treatment was published [28] . The median PFS was 22.0 months in immunotherapy group (4.3 months in control group).…”
Section: Discussionmentioning
confidence: 99%
“…The general ORR of chemotherapy in AFPGC was reported to be 8.3% to 66.7% as a first-line therapy, which is quite diverse among different reports because of the small sample sizes. A report of 7 advanced AFPGC patients treated with immunotherapy plus chemotherapy compared with 14 patients as control treated with chemotherapy with or without herceptin/apatinib as first-line treatment was published [28] . The median PFS was 22.0 months in immunotherapy group (4.3 months in control group).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no specific treatment for these special subtype, thus following treatment concepts of common gastric cancer (21). However, preliminary data suggest that patients with AFPproducing gastric cancer and hepatoid adenocarcinoma of the stomach may benefit from PD-1 checkpoint inhibitor combined with chemotherapy (21). In our case, systemic therapy with Capecitabine, Oxaliplatin and Trastuzumab was initiated based on positive IHC expression of HER2/ Neu and β-HCG.…”
Section: Discussionmentioning
confidence: 94%
“…AFP-positive gastric cancers can be classified into four subtypes including the hepatoid, yolk sac tumor, fetal gastrointestinal and mixed type (20). Currently, there is no specific treatment for these special subtype, thus following treatment concepts of common gastric cancer (21). However, preliminary data suggest that patients with AFPproducing gastric cancer and hepatoid adenocarcinoma of the stomach may benefit from PD-1 checkpoint inhibitor combined with chemotherapy (21).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, GS and CIN GC are generally considered to have poor therapeutic response to ICIs treatment, however, ICIs combined chemotherapy seems to function well in the clinical practice of HAS treatment [11] . A portion of HAS patients with TP53+ status may be one of the plausible explanations for this particular phenomenon, and these patients would be likely to exhibit a good response to ICIs therapy.…”
Section: Discussionmentioning
confidence: 99%
“…attempted to identify the molecular characteristics and targets of HAS. Although these studies reported that most HAS patients had refractory malignancies with microsatellite stability (MSS) [ 5 , 7 ], favorable disease control from ICIs combined chemotherapy was observed [11] .These findings suggest that HAS is a genetically distinct subgroup of GC, and the reevaluation of molecular signatures and current protocols will contribute to a better understanding of the pathogenesis of HAS and development of precision therapies.…”
Section: Introductionmentioning
confidence: 99%